Ethnomatematics-Based Mobile Learning Design to Improve Self-Regulated Learning - Wikan Budi Utami; Saida Ulfa; Henry Praherdhiono Praherdhiono (FKIP Universitas Lampung, 2022)
This study aims to produce ethnomatematic-based mobile learning that can be implemented so that it can improve student self-regulated learning. The research design used was the pre and posttest group design. The experimental and control groups will be given a pretest before treatment and a posttest after treatment. The population used was elementary school students and the sample used was 439 consisting of 215 students from the experimental class and 224 students from the control class. Data analysis in this study used statistical data processing software IBM SPSS version 27. Based on the summary of the results of the independent t test, the value of Sig. (2-tailed) on the posttest data of <0.001. This value is smaller than the specified significance level of 0.05. This means that the averages of the experimental and control groups at the time of the posttest were significantly different. The results of the analysis of self-regulated learning show that the analysis carried out on self regulated learning only obtained complete data on 134 students from the experimental class and 134 from the control class. The research results in the experimental class show that the learning planning variable is in the high category. The conclusion from this research is that the results of learning with mobile learning with ethnomathematics content on self-regulated learning can improve student learning outcomes so that they can be implemented in schools.Keywords: mobile learning, ethnomathematics, self-regulated learning, learning outcomes.DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1692-1700